Progression of intermediate age-related macular degeneration with proliferation and inner retinal migration of hyperreflective foci - Christenbury, Joseph G; Folgar, Francisco A; O'Connell, Rachelle V; Chiu, Stephanie J; Farsiu, Sina; Toth, Cynthia A (Ophthalmology (Rochester, Minn.), 2013)
Drusen and migrating retinal pigment epithelium have been associated with hyperreflective foci (HF) detected by spectral-domain optical coherence tomography (SD-OCT). This study sought to quantify the change in intraretinal HF distribution and its correlation with age-related macular degeneration (AMD) disease progression. Prospective observational study from the multicenter Age-Related Eye Disease Study 2 (AREDS2) Ancillary SD-OCT Study. Patients (n=299) with 1 enrolled eye with intermediate AMD and baseline SD-OCT, followed by SD-OCT imaging at 1-year and 2-year visits. The number and location of HF were scored in SD-OCT scans of all 299 eyes. The change in transverse (horizontal) and axial (vertical) distribution of HF in the macula were evaluated with pairwise signed-rank tests. Two-year inner retinal HF migration was determined by the change in HF-weighted axial distribution (AxD) score calculated for each eye. The correlation of HF with SD-OCT features of AMD progression was evaluated with logistic regression analysis. The mean change in number of HF, transverse and axial distribution of HF in the macula, and AxD per eye. In 299 study eyes, the 2-year increase in the number of HF (P<0.001) and the AxD (P<0.001) per eye represented longitudinal proliferation and shift to inner retinal layers, respectively. Eyes with geographic atrophy (GA) at 2 years were correlated with the presence of baseline HF (P<0.001; odds ratio [OR], 4.72; 95% confidence interval [CI], 2.43-9.80), greater number of baseline HF (P<0.001; OR, 1.61 per HF; 95% CI, 1.32-2.00), and greater baseline AxD (P<0.001; OR, 1.58 per AxD point; 95% CI, 1.29-1.95). Proliferation and inner retinal migration of SD-OCT HF occurred during follow-up in eyes with intermediate AMD. These characteristics were associated with greater incidence of GA at year 2; therefore, SD-OCT HF proliferation and migration may serve as biomarkers for AMD progression. Proprietary or commercial disclosure may be found after the references.